Camera traps in animal ecology methods and analyses - O'Connell, Allan F.; Nichols, James D.; Karanth, K. Ullas 1948-.; International Mammalogical Conference Sapporo, Japan) 2005 (Tokyo Springer, 2011)
Remote photography and infrared sensors are widely used in the sampling of wildlife populations worldwide, especially for cryptic or elusive species. Guiding the practitioner through the entire process of using camera traps, this book is the first to compile state-of-the-art sampling techniques for the purpose of conducting high-quality science or effective management. Chapters on the evaluation of equipment, field sampling designs, and data analysis methods provide a coherent framework for making inferences about the abundance, species richness, and occupancy of sampled animals. The volume introduces new models that will revolutionize use of camera data to estimate population density, such as the newly developed spatial capture?recapture models. It also includes richly detailed case studies of camera trap work on some of the world?s most charismatic, elusive, and endangered wildlife species. Indispensible to wildlife conservationists, ecologists, biologists, and conservation agencies around the world, the text provides a thorough review of the subject as well as a forecast for the use of remote photography in natural resource conservation over the next few decades.
A history of camera trapping / Thomas E. Kucera, Reginald H. Barrett -- Evaluating types and features of camera traps in ecological studies : a guide for researchers / Don E. Swann, Kae Kawanishi, Jonathan Palmer -- Science, conservation, and camera traps / James D. Nichols, K. Ullas Karanth, Allan F. O'Connell -- Behavior and activity patterns / Andrew S. Bridges, Andrew J. Noss -- Abundance, density and relative abundance : a conceptual framework / Timothy G. O'Brien -- Estimating tiger abundance from camera trap data : field surveys and analytical issues / K. Ullas Karanth, James D. Nichols, N. Samba Kumar -- Abundance/density case study : jaguars in the Americas / Leonardo Maffei ... [et al.] -- Estimation of demographic parameters in a tiger population from long-term camera trap data / K. Ullas Karanth ... [et al.] -- Hierarchical spatial capture-recapture models for estimating density from trapping arrays / J. Andrew Royle, Beth Gardner -- Inference for occupancy and occupancy dynamics / Allan F. O'Connell, Larissa L. Bailey -- Species richness and community dynamics : a conceptual framework / Marc K?ery -- Estimation of species richness of large vertebrates using camera traps : an example from an Indonesian rainforest / Timothy G. O'Brien, Margaret F. Kinnaird, Hariyo T. Wibisono -- Camera traps in animal ecology and conservation : what's next? / James D. Nichols, Allan F. O'Connell, K. Ullas Karanth.
Outgrowth of the 9th International Mammalogical Conference held in Sapporo, Japan, in Aug. 2005. Cf. pref.
Electronic reproduction.
Keywords: Animal ecology; Wildlife photography; Wildlife conservation; Animal ecology -- Research -- Methodology; Animal ecology -- Remote sensing; Photography in wildlife monitoring; Wildlife research -- Methodology; Photography -- Scientific applications; Animal populations -- Monitoring -- Methodology; Ecology -- Methodology; Photography in environmental monitoring; Electronic books; Electronic books